PENANGANAN PEMALSUAN PASPOR DI BANDARA: STUDI KASUS DAN STRATEGI KEIMIGRASIAN DI INDONESIA - Zakhran Syah, Razka; Yedida Ardi, Imma; Ryanindityo, Mochammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the cases of passport forgery at Indonesia's international airports and the immigration law strategies implemented to address these cases. Passport forgery is a serious criminal act that threatens national security and undermines the immigration system. This research employs a descriptive qualitative approach based on literature review. Data were collected from secondary sources such as scientific journals, official reports, and legal documents related to passport forgery. The content analysis method was used to identify patterns, challenges, and immigration law enforcement strategies in Indonesia. The results indicate that, despite advancements in the Indonesian immigration system, challenges remain in detecting and handling forged passports, especially at international airports. Therefore, enhancing detection technologies and fostering stronger collaboration between relevant agencies are necessary. This study also provides policy recommendations to strengthen immigration law enforcement in combating passport forgery in the future. The findings are expected to contribute to enhancing the immigration system in Indonesia.